HISTORISITAS ATURAN DAN TUJUAN PERCERAIAN DALAM PERUNDANG-UNDANGAN KELUARGA ISLAM INDONESIA DAN NEGARA-NEGARA MUSLIM - Rasyid, Arbanur; Ridwan, Muhammad; Lubis, Maulana Arafat (Jurnal el-Qanuniy: Jurnal Ilmu-Ilmu Kesyariahan dan Pranata Sosial, 2021)
This paper talks about problems in the family, especially those related to divorce according to Classical Fiqh and looks at how relevant it is to be applied in Indonesia, using the perspective of Human Rights, and the Anti-Discrimination Law, as well as the form of government intervention in this issue. The dissolution of a marriage caused by divorce can occur due to talak or based on a divorce suit. The Indonesian state ratifies that divorce can only be carried out in front of the Religious Court (PA) after the Religious Court tried and failed to reconcile the two parties. Whereas in Islamic countries such as Brunei, divorce is still recognized out of court, although it is recommended to register after divorce (talak). Brunei still recognizes triple talaq at once. In the matter of divorce, the Singapore law only regulates the suffocating or squabbling that occurs between spouses. For cases of dispute, the judge will send a judge to reconcile the two. The Philippines requires registration which functions as administrative data. Turkey, with The Ottoman Law Of Family Rights (Qonun Qarar Al Huquq Al-'Ailah Al-Ottoman) in 1917 article 38, stipulates that it is permissible for a wife to divorce a wife in the form of her husband not being allowed to remarry another woman. The Lebanese Druze Law Number 24 of 1948 stipulates that divorce only occurs through a judge's decision in the presence of two people. Syria, in Law no. 34 of 1975 stipulates that the husband has the right to give full divorce if he is at least 18 years old. Tunisian Law No. 40 1957 stipulates that divorce only occurs in Court. In Iraq it is stipulated that husbands who will divorce their wives are encouraged but are not required to report to the court.